Effect of Landform on the Distribution of Metroxylon sagu Habitat in Yapen Islands, Papua Province, Indonesia - Petrus Abraham Dimara; Amilda Auri (Department of Forestry, Faculty of Agriculture, University of Lampung, 2023)
Sago palm (Metroxylon sagu) plays a vital role in the Papuan indigenous community’s social, economic, and cultural life. It is a source of staple food, household income, and embedded cultural values. This research aimed to determine the extent of sago palm habitat spread using spatial data. The classification method and multispectral imaging were used by employing satellite imagery (Landsat 8 and Quick Bird) and field surveys. The sago forest coverage in Yapen islands was 87.73%, located between 9–50 masl, covering 9,456.26 ha. The results revealed that 43.53% of the habitat lies in the inclination of 2–8% (extreme gentle slope), covering 4,692.45 ha. Sago forest was found in a gleysol soil type with precipitation of 3,000-3,100 mm. The sago forest distances of 0–250 m and 251–500 m to the coastline showed that the habitat covers an area of 153.87 ha and 368.19 ha. The preferable area in this category is Raimbawi Subdistrict, followed by Kosiwo, and the less suitable area, or the marginal land, is in Windesi Subdistrict. Keywords: Alternative crop, Metroxylon sagu, sago, spatial distribution, Yapen Islands